Cross‐sectional analysis of healthy individuals across decades: Aging signatures across multiple physiological compartments - Moaddel, Ruin; Ubaida‐Mohien, Ceereena; Tanaka, Toshiko; Tian, Qu; Candia, Julián; Moore, Ann Zenobia; Lovett, Jacqueline; Fantoni, Giovanna; Shehadeh, Nader; Turek, Lisa; Collingham, Victoria; Kaileh, Mary; et al. (Aging cell, 2024)
The study of age‐related biomarkers from different biofluids and tissues within the same individual might provide a more comprehensive understanding of age‐related changes within and between compartments as these changes are likely highly interconnected. Understanding age‐related differences by compartments may shed light on the mechanism of their reciprocal interactions, which may contribute to the phenotypic manifestations of aging. To study such possible interactions, we carried out a targeted metabolomic analysis of plasma, skeletal muscle, and urine collected from healthy participants, age 22–92 years, and identified 92, 34, and 35 age‐associated metabolites, respectively. The metabolic pathways that were identified across compartments included inflammation and cellular senescence, microbial metabolism, mitochondrial health, sphingolipid metabolism, lysosomal membrane permeabilization, vascular aging, and kidney function. A targeted metabolomic analysis of plasma, skeletal muscle, and urine from healthy participants was carried out to compare and contrast metabolite changes with aging across and within compartments. The metabolic pathways that were identified included inflammation and cellular senescence, microbial metabolism, mitochondrial health, sphingolipid metabolism, lysosomal membrane permeabilization, vascular aging, and kidney function.